Morphological study of telocytes in the left atrium in patients with long-term persistent atrial fibrillation - L. B. Mitrofanova; A. O. Khazratov; A. V. Gurshchenkov; A. M. Osadchii; A. N. Gorshkov; B. E. Galkovsky (Российский кардиологический журнал)
The telocytes were found in the human atria in 2005. Atrial fibrillation (AF) is the most common heart rhythm disorder, accompanied by inflammation and fibrosis, however, the morphological analysis of telocytes in this pathology has not yet been performed.Aim. To make morphological analysis of left atrial telocytes in patients with longterm persistent AF.Material and methods. The study was based on the left atrial (LA) wall of 10 patients with AF, 10 without AF (autopsy material) and LP fragments of 2 patients with AF (surgical material). A histological, immunohistochemical, and ultrastructural study, telocyte culture isolation, and confocal laser microscopy were performed.Results. The presence of telocytes in the LA was confirmed. Morphometric analysis revealed that the average number of telocytes in the LP was significantly less by 3 times in patients with AF than without it (2,7±1,1 vs 8,2±3,0 with x400). Correlation analysis revealed significant negative associations of the number of telocytes with AF, fibrosis, lipomatosis, and inflammation.Conclusion. The development of inflammation and fibrosis in AF is accompanied by the loss of telocytes.